A General Question about Sentence Classification in Chinese - Akramdjan Abilevich Karimov (Researchparks Publishing, 2022)
The scientific views of Russian, Chinese and American scientists on the issue of dividing general interrogative sentences into subtypes in Chinese studies were critically analyzed, and a classification of general interrogative sentences corresponding to Chinese language phenomena was given both theoretically and practically. In addition, it was recommended to divide interrogative sentences in Chinese into three types.